2019
DOI: 10.1590/1980-5373-mr-2018-0868
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Mechanical Properties of Sealing Mortar with Partial Replacement of Portland Cement by Stone Crusher Waste

Abstract: Civil construction is one segment responsible for major environmental and social impacts. Among its raw materials, Portland cement, which is produced by the burning and subsequent grinding of a composition of clays and limestones. This manufacturing process causes great environmental damage, both by the exploitation of deposits and by the process of clinkering (burning of raw materials), which emits a significant amount of CO 2 in the atmosphere. Therefore, there is a need for research on materials that reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
1
0
Order By: Relevance
“…The use of solid waste in construction materials has grown lately [9]. The use of by-products generated in the sector itself is absorbed, as well as the waste from other productive sectors.…”
Section: Introductionmentioning
confidence: 99%
“…The use of solid waste in construction materials has grown lately [9]. The use of by-products generated in the sector itself is absorbed, as well as the waste from other productive sectors.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier research indicates that the addition of Nano silica (NS) particles in cement mortar improves the mechanical strength of the specimen more than the Silica Fume (SF) and Fly Ash (FA) concrete showed Biricik and Sarier (2014). Dossena et al (2019) indicated that when cement was replaced by 10% of crusher residue, the strength of the mortar increased; however, when the replacement was above 10% the strength decreased. Using Taguchi Grey relationship analysis, the 2% nano-silica was optimized in cement mortar, and the study findings revealed that the compressive strength increased and water absorption reduced [9].…”
Section: Introductionmentioning
confidence: 99%